1985
DOI: 10.1093/nar/13.15.5591
|View full text |Cite
|
Sign up to set email alerts
|

Exon mutations that affect the choice of splice sites used in processing the SV40 late transcripts

Abstract: ABSTRACrThe spliced species of late SV40 RNAs present in the cytoplasm of cells infected with various wild-type and mutant strains of SV40 that differ in their leader regions were determined using a novel modification of the primer extension method and the S1 nuclease mapping technique. These data indicated that mutations within the first exon of the late RNAs can affect dramatically the utilization of downstream donor and acceptor splice sites. In one instance, a ten base pair insertion within the predominant… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
53
0

Year Published

1987
1987
2008
2008

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 100 publications
(53 citation statements)
references
References 30 publications
(15 reference statements)
0
53
0
Order By: Relevance
“…Furthermore, by linker scanning analysis, we found that at least three distinct sequences within exon 4 are necessary for the tissue-specific splicing. Effects of exon sequences on splicing have been described previously (Somasekhar and Mertz, 1985;Reed and Maniatis, 1986;Mardon et al, 1987;Cooper et al, 1988;Kakizuka et al, 1988), although in none of these cases were the effects of exon sequences on tissue-specificity of splicing studied. From the sequence data alone, it is not obvious how the exon sequences might affect splicing.…”
Section: Discussionmentioning
confidence: 95%
“…Furthermore, by linker scanning analysis, we found that at least three distinct sequences within exon 4 are necessary for the tissue-specific splicing. Effects of exon sequences on splicing have been described previously (Somasekhar and Mertz, 1985;Reed and Maniatis, 1986;Mardon et al, 1987;Cooper et al, 1988;Kakizuka et al, 1988), although in none of these cases were the effects of exon sequences on tissue-specificity of splicing studied. From the sequence data alone, it is not obvious how the exon sequences might affect splicing.…”
Section: Discussionmentioning
confidence: 95%
“…Pre-mRNA splicing in nematodes includes both conventional cis-splicing as well as trans-splicing (for reviews, see Blumenthal & Steward, 1997;Nilsen, 1997)+ In the trans-splicing reaction, the 59 exon is donated from a separate transcript, the spliced leader RNA (SL RNA), which contains hallmarks of the small nuclear RNAs (snRNAs) involved in standard splicing reactions (Bruzik et al+, 1988;Thomas et al+, 1988;Nilsen et al+, 1989)+ Required cofactors for trans-splicing include the U2, U5, and U4/U6 small nuclear ribonucleoprotein particles (snRNPs; Hannon et al+, 1991;Maroney et al+, 1996) as well as serine/arginine-rich splicing factors (SR proteins; Sanford & Bruzik, 1999b)+ Although extensive similarities between the required cofactors for cis-and trans-splicing have been documented, there is a clear difference in the necessity for U1 snRNP at the 59 splice site (Hannon et al+, 1991)+ Thus, the transsplicing reaction naturally occurring in nematodes has been deemed independent of the need for the 59 end of U1 that normally base pairs with the 59 splice site+ A large body of work has elucidated many of the cis-acting elements involved in pre-mRNA splicing in higher eukaryotes (for review, see Reed & Palandjian, 1997)+ These include the 39 splice site AG dinucleotide whose necessity is coupled to the length of the preceding polypyrimidine tract (Reed, 1989)+ Because trans-splicing substrates lack the potential for spliceosomal interactions across an intron, they have been suggested to be exquisitely AG-dependent at the 39 splice site (Wu et al+, 1999)+ Additionally, the effects of 39 exonic sequences on splicing of an upstream intron were documented over a decade ago (Somasekhar & Mertz, 1985;Reed & Maniatis, 1986)+ More recently, discrete elements termed exonic splicing enhancers (ESEs) have been identified that promote upstream splicing in both alternatively spliced (for review, see Wang & Manley, 1997) as well as constitutive premRNAs (Schaal & Maniatis, 1999a)+ Many of these ESEs have been shown to interact with SR proteins+ The two major domains of SR proteins, an N-terminal RNA recognition motif(s) (RRM) and a C-terminal region rich in RS dipeptides, allow for RNA binding and protein-protein interactions, respectively (for review, see Graveley, 2000)+ In addition to the predominantly purinerich ESEs, several examples of other general classes of splicing enhancers have been identified+ These include the A/C-rich splicing enhancers (Coulter et al+, 1997), intronic splicing enhancers (for examples, see , and splicing enhancers that modulate 59 splice site usage (Humphrey et al+, 199...…”
Section: Introductionmentioning
confidence: 99%
“…The choice between these mutually exclusive sites is dependent on cell-specific, trans-acting factors. Additional sites required in cis for splice site selection have been implicated in studies on other loci, including the branch site (Noble et al 1987;Fu et al 1988) and sequences within the alternatively spliced exons (Somasekhar and Mertz;Mardon et al 1987;Barone et al 1989;Hampson et al 1989;Laski and Rubin 1989;Streuli and Saito 1989). This diversity of regions involved in regulating splice choice suggests that multiple mechanisms exist for controlling RNA processing.…”
mentioning
confidence: 99%